BUSINESS SECURITY AND DIGITAL THREATS - Rashidov Shohruh Kamoliddin ugli (Modern American Journals, 2025)
This article explores the increasing concern about business security amidst the rising wave of digital threats. As businesses rapidly digitize, vulnerabilities such as ransomware, phishing, and insider threats have become prevalent. The paper presents theoretical insights, practical strategies, real-world cases, and statistical trends to help organizations strengthen their cybersecurity posture.
Keywords: Cybersecurity, digital threats, business security, ransomware, data protection, risk management, phishing attacks.